Effect of homogenization on anodic film and electrochemical behavior of an A535 alloy after sealing with stearic sealant - Chankitmunkong, Suwaree; Eskin, Dmitry G.; Limmaneevichitr, Chaowalit; Pandee, Phromphong; Kengkla, Nattarat; Athchasiri, Jirakit; Tanawansombat, Tanawat; Parnlasarn, Napadol; Diewwanit, Onnjira (Light metals 2022)
Almag 35 (A535) is a commercial aluminum alloy intended for a number of marine components, which is mainly justified by its excellent castability and corrosion resistance. However, the most important factor for corrosion resistance is the formation of intermetallics that can lead the defects in the oxide film and substrate, as well as activate the corrosion reaction. The characteristics of a sealant on the anodic film were investigated in this work. The alloy was subjected to homogenization at 400 degrees C for 5 h to improve the uniformity of the anodic oxide film due to the decreased number of intermetallics as a result of dissolving in the matrix. It also improved the hardness of this alloy. Electrochemical measurements were conducted to investigate the corrosion behavior. The effects of intermetallics and stearic sealing on the characteristics of the oxide layer are discussed. The decrease in the number of intermetallics can lead to reduced corrosion current density (I-corr) and increased potential corrosion (E-corr), which results in a lower corrosion rate of this alloy.